Effect of leaf phenology and morphology on the coordination between stomatal and minor vein densities - Zhao, Wanli; Fu, Peili; Mao, Qinggong; Liu, Guolan; Li, Yuanqiu; Xia, Jiangbao; Zhao, Ping (Frontiers in Plant Science, 2023)
Leaf phenology (evergreen vs deciduous) and morphology (simple vs compound) are known to be related to water use strategies in tree species and critical adaptation to certain climatic conditions. However, the effect of these two traits and their interactions on the coordination between minor vein density (MVD) and stomatal density (SD) remains unclear. In this study, we examined the leaves of 108 tree species from plots in a primary subtropical forest in southern China, including tree species with different leaf morphologies and phenologies. We assessed nine leaf water related functional traits for all species, including MVD, SD, leaf area (LA), minor vein thickness (MVT), and stomatal length (SL). The results showed no significant differences in mean LA and SD between either functional group (simple vs compound and evergreen vs deciduous).However, deciduous trees displayed a significantly higher mean MVD compared to evergreen trees. Similarly, compound leaved trees have higher (marginally significant) MVD than simple leaved trees. Furthermore, we found that leaf morphology and phenology have significantly interactive effects on SL, and the compound-leafed deciduous trees exhibited the largest average SL among the four groups. There were significant correlations between the MVD and SD in all different tree groups, however, the slopes and interceptions differed within both morphology and phenology. Our results indicate that MVD, rather than the SD, may be the more flexible structure in supporting the coordination between leaf water supply and demand in different leaf morphology and phenology. The results of the present study provide mechanistic understandings of functional advantages of different leaf types, which may involve in species fitness in community assembly and divergent responses to climate changes.